Anmeldelser - Jensen, Eva Maria (Danish Yearbook of Musicology, 2005)
Review of: Siglind Bruhn: Saints in the Limelight. Representations of the Religious Quest on the Post-1945 Operatic Stage. Dimension & Diversity Series, 5; Hillsdale, NY: Pendragon Press, 2003.